CAN THE USE OF FOUR SUPPOSITIONS AND TWO TECHNIQUES OF CHANGE ASSOCIATED WITH NEURO-LINGUISTIC PROGRAMMING (NLP) ENHANCE THE EXPERIENCE AND PERCEPTIONS ABOUT LEARNING FOR BOYS IN POST-16 EDUCATION? - Kudliskis, Voldis (International Journal of Research -GRANTHAALAYAH, 2023)
Living Educational Theory (LET), which sits within the interpretivist paradigm, provides pragmatic enquiries in real life educational contexts. This form of research provides a platform for examining four suppositions and two Techniques of Change associated with neuro-linguistic programming (NLP) particularly in the context of boys’ engagement with learning. NLP is proposed as a powerful personal development method. However, the credibility of NLP is questioned due to limited research-based evidence. Four NLP suppositions and two NLP Techniques of Change are examined. Thereafter, a description of an exploratory study into how these suppositions and Techniques of Change may enhance engagement with learning is provided. The study utilised a single method (semi-structured interview) approach. It is a single-site, multi-voice study capturing the perceptions of NLP, for boys in post-16 education, situated in a rural community college. ‘Positions of Consensus’ and individual narratives are explored and suggest that four suppositions and two Techniques of Change may enhance boys’ experiences and perceptions about learning. Possibly these NLP strategies may be helpful at an indirect level in enhancing boys’ engagement with learning in post-16 education. Inferences provide tentative evidence that these suppositions and Techniques of Change may aid engagement with learning in this specific context. It is suggested that these NLP suppositions and Techniques of Change could be implemented, via a cost-effective training programme, to enhance engagement with learning and to drive a culture of excellence in schools and FE colleges.